(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The increasing demand for concrete in modern construction has raised concerns regarding the environmental impact and depletion of natural resources, particularly the excessive use of conventional fine aggregates such as manufactured or mined sand. As a response to these concerns, this study explores the potential of using river sand as a sustainable alternative for conventional fine aggregates in concrete. River sand, due to its natural origin, generally possesses well-rounded particles, better workability, and uniform gradation, which can influence the performance characteristics of concrete in a positive way. To assess the effectiveness of river sand as a fine aggregate, an experimental approach was adopted. Three concrete mix designs were prepared: the first mix used 100% conventional sand and served as the control; the second contained a 50:50 combination of conventional and river sand; and the third used river sand exclusively. Each mix maintained a consistent water-cement ratio and similar aggregate grading to ensure accurate comparison. The concrete specimens were cast and cured for 28 days under controlled conditions before undergoing compressive strength testing according to standard procedures. The results of the experimental investigation demonstrated a clear trend: as the proportion of river sand increased, so did the compressive strength of the concrete. The mix containing 100% river sand exhibited the highest compressive strength, outperforming both the control and the 50% blend. This enhancement in strength can be attributed to the better particle distribution and packing density offered by river sand, which helps minimize internal voids and results in a more compact and stronger concrete structure. Moreover, the study highlights the environmental and economic benefits of adopting river sand in construction. Its widespread availability and natural properties reduce the need for processing and energy-intensive manufacturing, making it a cost-effective and eco-friendly option. The use of river sand can also ease the pressure on traditional sand sources, supporting resource conservation efforts. In conclusion, the findings of this study indicate that river sand is a viable and effective substitute for conventional fine aggregates in concrete, particularly in terms of enhancing compressive strength. Its incorporation in concrete mixtures not only improves mechanical performance but also aligns with sustainable construction practices, offering a dual benefit of strength and environmental responsibility. This positions river sand as a promising material for future developments in green and efficient building technologies.